2016
DOI: 10.1590/1807-3107bor-2016.vol30.0139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a dental care program on the quality of life of children with and without caries

Abstract: Impact of a dental care program on the quality of life of children with and without caries Abstract: The aim of the present study was to evaluate the long-term effects of the caries treatment provided by a dental care program on changes in schoolchildren's OHRQoL. A one-year follow-up was conducted with a sample of 372 children aged 8 to 10 years which were clinically examined and divided into two matched groups according to their caries experience: dental treatment group (DTG) and group without caries (GWC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…One possible explanation is the increased access to dental services available in the rural areas. Other studies have shown ( 20 ) that such trends can be found when people have increased access to dental services. Further study is needed to find an explanation for this anomaly in the data.…”
Section: Discussionmentioning
confidence: 92%
“…One possible explanation is the increased access to dental services available in the rural areas. Other studies have shown ( 20 ) that such trends can be found when people have increased access to dental services. Further study is needed to find an explanation for this anomaly in the data.…”
Section: Discussionmentioning
confidence: 92%
“…Nesse contexto, a integração ensinoserviço-comunidade pode contribuir para ampliação do acesso aos serviços de saúde, pois as faculdades, ao se tornarem referência de atenção odontológica à população, inclusive com a oferta de serviços especializados, podem complementar efetivamente as redes de saúde, conforme já observado em outras experiências no país 14,15 . Porém, é essencial o conhecimento da situação de saúde e do desempenho do sistema para o melhor planejamento das ações.…”
Section: Resultsunclassified
“…In addition, a higher percentage of children from this group also considered the health of their teeth/mouth as "excellent" after treatment, meaning that they probably acquired sufficient awareness to understand the benefits of dental treatment. 16 As OHES sessions were designed to increase knowledge on the relationship between health, disease, and quality of life, 7,10 the strategy provided understanding of their own oral problems and symptoms and the extent to which these symptoms may 'bother' and affect their daily activities, which were not sufficiently perceived before dental treatment. However, it is important to mention that contact with the health team was more frequent and intense with the OHES+ART group, totaling 5 or more sessions including OHES and ART procedures, which may have also favored this group.…”
Section: Discussionmentioning
confidence: 99%
“…7 Such strategies can encompass physical and mental health aspects aimed at providing learning experiences on health topics, developing personal skills, and promoting healthier behaviors. 9,10,11 Oral health programs can be especially relevant in primary school, a convenient place for changing unhealthy behaviors, particularly of groups in which healthy habits have not yet been established. 12 Atraumatic restorative treatment (ART) has been recommended by the World Health Organization (WHO) and the Pan American Health Organization (PAHO) as a minimal intervention procedure applicable at the public health level to manage dental caries.…”
Section: Introductionmentioning
confidence: 99%